Analysis of ZIS, Taxes, and Poverty Alleviation Fund Impacts on Poverty Rates in Indonesia - Aminanto, Muhamad Erda; Rohim, Ade Nur Rohim; Handayani, Tati (Dirham: Journal of Sharia Finance and Economics, 2026)
Purpose: This study examines the impact of Zakat, Infaq, and Sadaqah (ZIS), taxes, and poverty alleviation funds on poverty rates in Indonesia between 2013 and 2019. Methods: A quantitative approach was used with secondary data from national ZIS institutions (BAZNAS), the Directorate General of Taxes, and the Ministry of Social Affairs. Data were analyzed using multiple linear regression to assess the relationship between ZIS, taxes, poverty alleviation funds and poverty rates. Results: The findings indicate a significant positive effect of ZIS and taxes on poverty rates, suggesting that both variables contribute to higher poverty levels when they are inadequately managed. In contrast, the poverty alleviation fund showed no significant effect on poverty reduction. Among the three, taxes had the greatest influence on poverty rates, followed by the ZIS. Conclusion: This study concludes that taxes and the ZIS play a crucial role in addressing poverty in Indonesia. However, effective management and utilization of poverty alleviation funds are necessary to ensure a positive impact. Increased efficiency in fund allocation and distribution is vital for achieving significant poverty reduction. Limitations: This study is limited to the Indonesian context and focuses on three main variables: ZIS, taxes, and poverty alleviation funds. Future studies should explore comparative research across countries and incorporate other potential factors affecting poverty rates. Contribution: This study provides insights into the roles of the ZIS, taxes, and poverty alleviation funds in poverty reduction, offering recommendations for enhancing the effectiveness of these interventions.